2020
DOI: 10.1038/s41598-020-58129-w
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and Maternal Mental Health: A Randomised Controlled Trial among Pregnant Women with Obesity

Abstract: poor maternal mental health has been associated with a myriad of pregnancy and child health complications. obesity in pregnancy is known to increase one's risk of experiencing poor maternal mental health and associated physical and mental health complications. probiotics may represent a novel approach to intervene in poor mental health and obesity. We conducted this pre-specified secondary analysis of the Healthy Mums and Babies (HUMBA) randomised controlled trial to investigate whether probiotics would improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 67 publications
0
64
0
1
Order By: Relevance
“…After removal of 1,821 duplicates, titles and abstracts of 2,047 references were screened. At this stage, 54 full-text articles were judged to be potentially relevant, of which 4 articles satisfied the review eligibility criteria (33)(34)(35)(36). Of these, one reference (35) was a multiple publication of another trial (33) and, therefore, the systematic review included 3 unique studies (33,34,36) reported in 4 publications.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After removal of 1,821 duplicates, titles and abstracts of 2,047 references were screened. At this stage, 54 full-text articles were judged to be potentially relevant, of which 4 articles satisfied the review eligibility criteria (33)(34)(35)(36). Of these, one reference (35) was a multiple publication of another trial (33) and, therefore, the systematic review included 3 unique studies (33,34,36) reported in 4 publications.…”
Section: Search Resultsmentioning
confidence: 99%
“…The effectiveness of pregnancy use of probiotics, probiotics, and synbiotics to reduce the risk of mental health problems in the perinatal period is a relatively new area of research, with three trials published between 2016 and 2020. Studies were conducted in New Zealand (33,36) and Iran (34). Studies were funded by university (34), and research grants and industry partners (33,36).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The probiotic supplementation did not increase the incidence of adverse perinatal outcomes 14,17 . Although the beneficial effects of probiotics on perinatal metabolic diseases and the mental disorders have been described, 8,18–22 the efficiency on the interactions of vaginal microbiome during the pregnancy is yet lacking. The previous study did not support that taking probiotics was significantly beneficial to pregnancy 16 .…”
Section: Discussionmentioning
confidence: 95%